Silicon carbon material and preparation method thereof
By adopting a silicon-carbon material with a core-shell structure, the combination of porous carbon and silicon particles is used to control the pore distribution of the material and the quality of silicon, the problem of excessive expansion rate of the negative electrode material of the lithium-ion battery is solved, and the electrochemical performance of the material and the service life of the battery cell are improved.
Patent Information
- Application Number
- CN202411864645.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-05-02
AI Technical Summary
The expansion rate of the negative electrode materials of existing lithium-ion batteries is too high, resulting in cracking of SEI films, increasing side reactions and shortening of battery life.
The silicon carbon material adopts a core-shell structure, the core consists of porous carbon and silicon particles deposited on the porous carbon. The outer shell is a carbon layer covered on the outer surface of the porous carbon. By controlling the pore distribution of porous carbon and the mass of silicon particles, the structure and physical and chemical parameters of the material are optimized.
By reducing the expansion of silicon, reducing the occurrence of side reactions, improving the material's capacity and cycling performance, and extending the service life of the battery cell.
Smart Images

Figure BDA0005194030330000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a silicon-carbon material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high energy density, wide operating temperature, long cycle life, no memory effect, and environmental friendliness. They are widely used in power battery fields such as automobiles and electric bicycles, energy storage fields such as power grids, industrial energy storage, home energy storage, and communication energy storage, and 3C digital fields such as smart phones, laptops, smart wearable devices, and mobile power supplies. Therefore, it is urgent to develop a low-expansion silicon-carbon material.
[0003] The current commercial lithium battery negative electrode materials are mainly modified natural graphite and artificial graphite. Although the preparation technology is quite mature, its theoretical specific capacity is only 372mAh / g, which is difficult to meet the market demand for large-capacity lithium-ion batteries. Therefore, the current research and development of silicon-carbon negative electrodes with higher gram capacity is increasing. Although the capacity of silicon-carbon negative electrodes is very high, the expansion is very large. When fully charged, it can reach a volume expansion of about 300%. The current design of deposited silicon-carbon materials is not reasonable, and the expansion is large, which causes the SEI film of silicon-carbon materials that expands when lithium is embedded to crack, and the contact area between silicon and electrolyte increases. During charging and discharging, the increase in side reactions leads to a sharp increase in by-products, resulting in large expansion of the material, which reduces the service life of the battery cell.
[0004] Therefore, there is an urgent need to develop a low expansion silicon-carbon material. Summary of the invention
[0005] The purpose of the present invention is to provide a silicon-carbon material, which optimizes the structure and physicochemical parameters of the silicon-carbon material to suppress the problem of increased side reactions caused by silicon expansion.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A silicon-carbon material comprises a core and a shell, wherein the core comprises porous carbon and silicon particles supported on the porous carbon; the shell is a carbon layer coated on the surface of the core, wherein the pore volume of the porous carbon is 0.7 to 1.1 cm 3 / g, the porous carbon comprises micropores with a pore size of less than 2 nm, mesopores with a pore size of 2 to 50 nm, and macropores with a pore size of more than 50 nm;
[0008] Among them, in the pore distribution of the porous carbon, the micropores account for A%, the mesopores account for B%, and the macropores account for C%, 5<A / (B+C)<15, and A+B+C=1.
[0009] Preferably, the A% is 85% to 90%, the B% is 6% to 10%, and the C% is 1% to 5%.
[0010] Preferably, the particle size concentration of the silicon-carbon material satisfies the relationship: (Dv90-Dv10) / Dv50<1.
[0011] Preferably, the particle size Dv50 of the silicon-carbon material is 8 to 12 μm.
[0012] Preferably, the mass of the silicon particles is 46% to 53% of the total mass of the silicon-carbon material.
[0013] Preferably, the mass of the carbon layer is 3% to 12% of the total mass of the silicon-carbon material.
[0014] The present invention also provides a method for preparing the above silicon-carbon material, comprising the following steps:
[0015] S1, heating a carbon source in an inert gas for carbonization to obtain a carbon matrix;
[0016] S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix;
[0017] S3, vapor-depositing silicon on the porous carbon substrate to obtain the core;
[0018] S4, vapor-depositing carbon on the inner core to form a carbon coating layer to obtain the silicon-carbon material.
[0019] Preferably, the carbonization of S1 comprises carbonizing the carbon source at 900-1200° C. for 3-6 hours.
[0020] Preferably, the pore-forming of S2 includes mixing a carbon matrix with a pore-forming agent and calcining at 850-1000°C for 1-2h; preferably, the purification of S2 includes acid washing and water washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4h; preferably, the pore-forming agent is an alkaline pore-forming agent; preferably, the pore-forming agent includes at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore-forming agent is 1-2mol / L; preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix.
[0021] Preferably, the vapor-deposited silicon in S3 includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor-depositing silicon on the porous carbon substrate; preferably, the conditions for the vapor-deposited silicon are deposition at 350-450°C for 1-3h; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas includes silane gas; preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton.
[0022] Preferably, the vapor-deposited carbon of S4 includes passing a carbon source gas into a reaction device containing an inner core obtained from S3, and vapor-depositing carbon on the inner core; preferably, the carbon source gas of S4 includes acetylene; preferably, the conditions for vapor-depositing carbon are deposition at 550-600°C for 1-3h.
[0023] The present invention also provides a negative electrode sheet, comprising the above silicon-carbon material.
[0024] The present invention also provides a secondary battery, comprising the above-mentioned negative electrode sheet.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects: the silicon-carbon material of the present invention improves the gram capacity and cycle performance of the material by controlling the parameters of silicon and porous carbon, especially the void distribution of porous carbon; the core-shell structure of the prepared silicon-carbon material can also reduce the expansion of silicon and extend the service life of the battery cell. DETAILED DESCRIPTION
[0026] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] According to a first aspect of the present invention, a silicon-carbon material is provided, comprising a core and a shell, wherein the core comprises porous carbon and silicon particles supported on the porous carbon; the shell is a carbon layer coated on the surface of the core, wherein the pore volume of the porous carbon is 0.7 to 1.1 cm 3 / g, the porous carbon includes micropores with a pore size of less than 2nm, mesopores with a pore size of 2-50nm and macropores with a pore size of more than 50nm; wherein, in the pore distribution of the porous carbon, the micropores account for A%, the mesopores account for B%, the macropores account for C%, 5<A / (B+C)<15, and A+B+C=1.
[0028] The functions of the pores of different pore sizes in porous carbon are as follows: micropores mainly provide adsorption sites and increase capacitance, and mesopores serve as mass transfer channels and adapt to volume changes to alleviate the expansion of deposited silicon. Macropores are used for the diffusion of silane in the silicon deposition process to enhance deposition uniformity. The present invention optimizes the performance of porous carbon materials by rationally designing the proportion of the three types of pores and regulating the pore size distribution.
[0029] In some embodiments, the A% is 85% to 90%, specifically 85%, 86%, 87%, 88%, 89%, 90%, etc.; the B% is 6% to 10%, specifically 6%, 7%, 8%, 9%, 10%, etc.; the C% is 1% to 5%, specifically 1%, 2%, 3%, 4%, 5%, and may include but are not limited to the values listed above.
[0030] The particle size of the silicon-carbon material satisfies the relationship: (Dv90-Dv10) / Dv50<1. Satisfying the above relationship can enhance the concentration of the particle size distribution of the silicon-carbon material and enhance the uniformity of silicon deposition.
[0031] In some embodiments, the particle size Dv50 of the silicon-carbon material is 8 to 12 μm, and the specific surface area of the silicon-carbon material is 0.1 to 0.5 m 2 / g. The silicon-carbon material within the above range reduces the distance that the material expands outward when lithium is inserted.
[0032] In some embodiments, the mass of the silicon particles is 46% to 53% of the total mass of the silicon-carbon material, and the mass of the carbon layer is 3% to 12% of the total mass of the silicon-carbon material. Reducing the carbon content improves the material's initial efficiency, reduces the material's polarization, and reduces the material's expansion to a certain extent; the porous carbon structure can provide more space for the volume expansion of silicon, effectively alleviating the stress caused by the expansion. At the same time, the porous surface can promote the transmission of Li+ and electrons, reduce the charge transfer impedance, and thus improve the electrochemical performance.
[0033] According to a second aspect of the present invention, the present invention further provides a method for preparing the above silicon-carbon material, comprising the following steps:
[0034] S1, heating a carbon source in an inert gas for carbonization to obtain a carbon matrix;
[0035] S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix;
[0036] S3, vapor-depositing silicon on the porous carbon substrate to obtain the core;
[0037] S4, vapor-depositing carbon on the inner core to form a carbon coating layer to obtain the silicon-carbon material.
[0038] The carbonization of S1 includes carbonizing the carbon source at 900-1200° C. for 3-6 hours. When the temperature is lower than this, the carbon source cannot be carbonized better, resulting in too many heteroatoms in the carbonized carbon source, while too high a carbonization temperature will result in a loose structure of the obtained carbon source and poor structural stability.
[0039] The pore-forming of S2 includes mixing the carbon matrix with a pore-forming agent, calcining at 850-1000°C for 1-2h; preferably, the purification of S2 includes acid washing and water washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4h; preferably, the pore-forming agent is an alkaline pore-forming agent; preferably, the pore-forming agent includes at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore-forming agent is 1-2mol / L; preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix. The reason for purification is that more impurities and heteroatoms will be produced during the pore-forming process before cleaning, and the product obtained by acid dissolution and purification is carried out, and the excess residual alkali is washed and neutralized. Calcination is then carried out to further remove impurities and purify the porous carbon source by high-temperature heating in an inert gas, reduce heteroatoms, especially the content of oxygen atoms, so as to improve the first effect of the material in the battery.
[0040] The vapor deposition silicon of S3 includes placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor depositing silicon on the porous carbon substrate; preferably, the conditions for vapor deposition of silicon are 350-450°C for 1-3h; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas includes silane gas; preferably, the first protective gas includes at least one of helium, nitrogen, argon and krypton. Below this temperature, silane is difficult to be reduced and the production capacity is low. Above this temperature, nano-silicon is converted from amorphous silicon to crystalline silicon, resulting in anisotropy of expansion and increasing the expansion rate of the material; and too high a temperature is prone to generate chemically inert silicon carbide. The deposition time is generally 1-3 hours. If the time is too short, silicon cannot be completely deposited inside the porous carbon. If the time is too long, silicon is easily accumulated on the surface of the porous carbon, increasing the expansion of the material and shortening the service life of the battery cell. If the size of the deposited nano-silicon particles is too small, there will be more interfaces between silicon and carbon, more lithium ion transfer interfaces, greater impedance, and greater polarization of the material during use. If the size of the nano-silicon is too large, the uniformity of lithium embedding inside the silicon will be worse, and it will be easier to break.
[0041] In some embodiments of the present invention, the vapor deposition of carbon in S4 includes passing a carbon source gas into a reaction device containing the core obtained in S3, and vapor deposition of carbon on the core; preferably, the carbon source gas in S4 includes acetylene; preferably, the vapor deposition of carbon is carried out at 550-600° C. for 1-3 hours. The gaseous carbon source is deposited on the outer surface of the silicon-carbon deposit for carbon coating, thereby reducing the polarization of the material and further reducing the expansion of silicon.
[0042] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0043] Example 1
[0044] A silicon-carbon material with a core-shell structure, wherein the core comprises porous carbon and silicon deposited in the porous carbon; and the shell is a carbon layer covering the outer surface of the porous carbon. The pore volume of the porous carbon is 0.8 cm 3 / g, the pore distribution structure of porous carbon includes micropores, mesopores and macropores, among which micropores account for 85% (A%), mesopores account for 10% (B%), and macropores account for 5% (C%).
[0045] The preparation method of silicon carbon material is as follows:
[0046] Step 1: Carbonize phenolic resin (purchased from Shaoguan Derui Chemical Industry Co., Ltd., CAS: 9003-35-4) in a tubular furnace at 950° C. under a nitrogen atmosphere for 4 hours.
[0047] Step 2, the carbonized material obtained in step 1 is mixed with a potassium hydroxide solution with a concentration of 2 mol / L, and placed in a constant temperature device for calcination at 850°C for 1.5 h, with the amount of potassium hydroxide added being 15% of the mass of the carbonized material. After the reaction is completed, it is acid-washed, washed with water to neutrality, dried, calcined at 500°C for 4 h, and crushed to obtain D v Porous carbon with a diameter of 50 to 9.5 μm and a pore volume of 0.7 cm 3 / g, in the void distribution of porous carbon, micropores account for 85%, mesopores account for 10% and macropores account for 5%.
[0048] Step 3, placing the product obtained in step 2 in a rotary furnace, introducing a mixed gas of 20% by volume of protective gas and 80% by volume of silane gas, wherein the protective gas is a mixture of nitrogen and argon (volume ratio of 1:1), the temperature in the rotary furnace is 450°C, the deposition is 3 hours, and the deposition amount of silicon is 47% of the total mass of silicon and carbon.
[0049] Step 4: Place the product obtained in step 3 in a rotary kiln and perform chemical vapor deposition in a mixed atmosphere of protective gas nitrogen and organic gas source acetylene (the volume ratio of nitrogen to acetylene is 1:3), the deposition temperature is 600°C, the deposition time is 3 hours, and the deposition amount of the carbon layer is 7% of the total mass of silicon carbon, and finally obtain a particle size D V Silicon carbon material with DV50 of 9.5 μm and concentration of (DV90-DV10) / DV50=0.8.
[0050] Example 2
[0051] The difference from Example 1 is that the particle size D of the obtained silicon-carbon material is V 50 is 12 μm, and the D of the porous carbon is controlled by controlling the degree of pulverization of the porous carbon in step 2. v 50~12μm.
[0052] The rest is the same as in Example 1 and will not be described again here.
[0053] Example 3
[0054] The difference from Example 1 is that the particle size D of the obtained silicon-carbon material is V 50 is 8 μm, and the D of the porous carbon is controlled by controlling the degree of pulverization of the porous carbon in step 2. v 50~8μm.
[0055] The rest is the same as in Example 1 and will not be described again here.
[0056] Example 4
[0057] The difference from Example 1 is that the number of micropores in the obtained silicon-carbon material accounts for 88% of the total pore ratio of the silicon-carbon material, that is, the carbonized material obtained in step 1 is mixed with a potassium hydroxide solution with a concentration of 2 mol / L and placed in a constant temperature device for calcination at 850°C for 1 hour.
[0058] The rest is the same as in Example 1 and will not be described again here.
[0059] Example 5
[0060] The difference from Example 1 is that the number of micropores in the obtained silicon-carbon material accounts for 90% of the total pore ratio of the silicon-carbon material, that is, the carbonized material obtained in step 1 is mixed with a potassium hydroxide solution with a concentration of 2 mol / L and placed in a constant temperature device for calcination at 850°C for 0.8h.
[0061] The rest is the same as in Example 1 and will not be described again here.
[0062] Example 6
[0063] The difference from Example 1 is that the pore volume of the porous carbon obtained is 1.1 cm 3 / g, by mixing with the carbonized material using a potassium hydroxide solution with a concentration of 3 mol / L.
[0064] The rest is the same as in Example 1 and will not be described again here.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that the pore volume of the porous carbon obtained is 0.6 cm 3 / g, by mixing with the carbonized material using a potassium hydroxide solution having a concentration of 1.5 mol / L.
[0067] The rest is the same as in Example 1 and will not be described again here.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that the pore volume of the obtained silicon-carbon material is 1.2 cm 3 / g, by mixing with the carbonized material using a potassium hydroxide solution having a concentration of 3.5 mol / L.
[0070] The rest is the same as in Example 1 and will not be described again here.
[0071] Comparative Example 3
[0072] The difference from Example 1 is that the number of micropores in the obtained silicon-carbon material accounts for 75% of the total pore ratio of the silicon-carbon material, that is, the carbonized material obtained in step 1 is mixed with a potassium hydroxide solution with a concentration of 2 mol / L and placed in a constant temperature device for calcination at 850°C for 2.5 hours.
[0073] The rest is the same as in Example 1 and will not be described again here.
[0074] Comparative Example 4
[0075] The difference from Example 1 is that the number of micropores in the obtained silicon-carbon material accounts for 95% of the total pore ratio of the silicon-carbon material, that is, the carbonized material obtained in step 1 is mixed with a potassium hydroxide solution with a concentration of 2 mol / L and placed in a constant temperature device for calcination at 850°C for 0.5h.
[0076] The rest is the same as in Example 1 and will not be described again here.
[0077] Comparative Example 5
[0078] The difference from Example 1 is that the concentration of the obtained silicon-carbon material is 1.2, that is, (Dv90-Dv10) / Dv50>1. By changing the degree of pulverization, the difference between Dv90 and Dv10 of the particles is made greater.
[0079] The rest is the same as in Example 1 and will not be described again here.
[0080] Comparative Example 6
[0081] The difference from Example 1 is that in the obtained silicon-carbon material, the silicon deposited in the porous carbon accounts for 55% of the total mass of the silicon-carbon material.
[0082] The rest is the same as in Example 1 and will not be described again here.
[0083] Comparative Example 7
[0084] The difference from Example 1 is that there is no step 5 of carbon coating.
[0085] The rest is the same as in Example 1 and will not be described again here.
[0086] The silicon-carbon materials obtained in the above Examples 1 to 6 and Comparative Examples 1 to 7 were respectively subjected to the following performance tests:
[0087] The test method of capacity retention rate: at 25℃, take the battery cell with 800 cycles, charge it to 4.53V at 0.5C constant current and constant voltage, and cut off the rate at 0.05C; leave it for 5 minutes; discharge it to 3.0V at 0.2C constant current. Read the discharge capacity, and divide it by the initial capacity of the battery cell to get the capacity retention rate.
[0088] Expansion rate test method: Use a half-cell with a single-layer stack to fully discharge the pure silicon anode, allow it to be fully embedded with lithium, and then test the thickness of the electrode.
[0089] The expansion rate of pure silicon-carbon material = (thickness of the fully lithium-embedded anode sheet / thickness of the anode sheet after rolling-1) × 100%.
[0090] The specific steps are as follows:
[0091] First, assemble a single-layer stacked half-cell in the order of lithium sheet, diaphragm, anode sheet, diaphragm, and lithium sheet. Discharge to 50mV with 0.1C and let it sit for 5min. Charge to 1.5V with 0.1C and let it sit for 5min. Discharge to 50mV with 0.1C and let it sit for 5min, then discharge to 50mV with 0.01C. Disassemble the single-layer half-cell, take the anode sheet, and use a micrometer to measure 5 points at each position, up, down, left, right, and center of the electrode sheet, for a total of 50 points. The average value of the 50 points is taken as the full lithium embedding thickness.
[0092] The parameters and experimental results of the above-mentioned embodiments 1 to 6 and comparative examples 1 to 7 are shown in Table 1.
[0093] Table 1
[0094]
[0095] Analysis of results: It can be seen from the above table that the expansion rates of the embodiments within the scope of the present invention are better than those of the comparative examples, indicating that the carbon layer coated on the outer layer can effectively inhibit the expansion of silicon in the core material, and the pores of different sizes in the porous carbon leave sufficient buffer space for the volume expansion of silicon during the cycle, thereby reducing the expansion rate of silicon and extending the service life of the battery cell.
[0096] In summary, the present invention provides a silicon-carbon material, including porous carbon, silicon deposited in the porous carbon, and a carbon layer coated on the outer surface of the porous carbon. The layered structure is beneficial to alleviating the expansion of silicon during charging and discharging and is beneficial to improving the electrochemical properties of the material, reducing the contact area between the silicon-carbon material and the electrolyte, thereby reducing the occurrence of harmful side reactions during the charging and discharging process of the battery.
[0097] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A silicon-carbon material, characterized in that: The invention comprises a core and a shell, wherein the core comprises porous carbon and silicon particles supported on the porous carbon; the shell is a carbon layer coated on the surface of the core, wherein the pore volume of the porous carbon is 0.7 to 1.1 cm 3 / g, the porous carbon comprises micropores with a pore size of less than 2 nm, mesopores with a pore size of 2 to 50 nm, and macropores with a pore size of more than 50 nm; Among them, in the pore distribution of the porous carbon, the micropores account for A%, the mesopores account for B%, and the macropores account for C%, 5<A / (B+C)<15, and A+B+C=1.
2. The silicon-carbon material according to claim 1, characterized in that: The A% is 85% to 90%, the B% is 6% to 10%, and the C% is 1% to 5%.
3. The silicon-carbon material according to claim 1 or 2, characterized in that: The particle size concentration of the silicon-carbon material satisfies the relationship: (Dv90-Dv10) / Dv50<1.
4. The silicon-carbon material according to claim 3, characterized in that: The particle size Dv50 of the silicon-carbon material is 8 to 12 μm.
5. The silicon-carbon material according to claim 1, characterized in that: The mass of the silicon particles is 46% to 53% of the total mass of the silicon-carbon material.
6. The silicon-carbon material according to claim 1, characterized in that: The mass of the carbon layer is 3% to 12% of the total mass of the silicon-carbon material.
7. A method for preparing a silicon-carbon material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, heating a carbon source in an inert gas for carbonization to obtain a carbon matrix; S2, forming pores in the carbon matrix and purifying the carbon matrix to obtain a porous carbon matrix; S3, vapor-depositing silicon on the porous carbon substrate to obtain the core; S4, vapor-depositing carbon on the inner core to form a carbon coating layer to obtain the silicon-carbon material.
8. The method for preparing the silicon-carbon material according to claim 7, characterized in that: The carbonization of S1 comprises carbonizing the carbon source at 900-1200° C. for 3-6 hours; And / or, the pore-forming of S2 comprises mixing a carbon matrix with a pore-forming agent, and calcining at 850-1000°C for 1-2h; preferably, the purification of S2 comprises acid washing and water washing the calcined product to neutrality, and then calcining at 500-600°C for 3-4h; preferably, the pore-forming agent is an alkaline pore-forming agent; preferably, the pore-forming agent comprises at least one of sodium hydroxide and potassium hydroxide; preferably, the concentration of the pore-forming agent is 1-2mol / L; preferably, the amount of the pore-forming agent added is 8%-15% of the mass of the carbon matrix; And / or, the vapor deposition of silicon in S3 comprises placing a porous carbon substrate in a reaction device, introducing a first mixed gas containing a first protective gas and a silicon source gas, and vapor depositing silicon on the porous carbon substrate; preferably, the vapor deposition of silicon is carried out under conditions of 350-450° C. for 1-3 hours; preferably, the content of the first protective gas is 10%-30% of the volume of the first mixed gas; preferably, the silicon source gas comprises silane gas; preferably, the first protective gas comprises at least one of helium, nitrogen, argon and krypton; And / or, the vapor-deposited carbon of S4 includes passing a carbon source gas into a reaction device containing the inner core obtained in S3, and vapor-depositing carbon on the inner core; preferably, the carbon source gas of S4 includes acetylene; preferably, the conditions for the vapor-deposited carbon are deposition at 550-600°C for 1-3h.
9. A negative electrode sheet, characterized in that: The invention comprises the silicon-carbon material as described in any one of claims 1 to 6.
10. A secondary battery, characterized in that: Including the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Manufacture of silicon-carbon composites
CN116323482A
Negative electrode material and preparation method and application thereof
CN116936811A
Carbon material, negative electrode material and preparation method thereof, and battery
CN117497764A
Negative electrode material and preparation method and application thereof
CN117790711A
Negative active particle and preparation method thereof, battery and electronic equipment
CN118039846A